ANALISIS PENGARUH EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI (STUDI PERBANDINGAN INDONESIA DAN THAILAND) - Hendra Kusuma; Fidanti Pramay Sheilla; Nazaruddin Malik (Universitas Ahmad Dahlan, 2020)
This study discusses export growth and its importance to the economic growth of comparative studios between Indonesia and Thailand from 1979 - 2018. The method used is multiple linear regression analysis to see the effect of the independent variables on the resulting dependent variable. The results showed that the f-statistics test of Indonesian exports did not have a significant effect with the direction of a negative relationship on economic growth. Thai exports also have no significant effect on the economy with a positive direction of relations. This is because the raw materials produced from export products are not entirely from within the country and the supported products are still primary products. In addition, the company's competitiveness in the use of technology for export activities is still lacking. While imports in Indonesia, and imports in Thailand have a significant influence on economic growth.